The case for induced pluripotent stem cell‐derived cardiomyocytes in pharmacological screening. (25th April 2013) - Khan, Jaffar M; Lyon, Alexander R; Harding, Sian E
Abstract : The current drug screening models are deficient, particularly in detecting cardiac side effects. Human stem cell‐derived cardiomyocytes could aid both early cardiotoxicity detection and novel drug discovery. Work over the last decade has generated human embryonic stem cells as potentially accurate sources of human cardiomyocytes, but ethical constraints and poor efficacy in establishing cell lines limit their use. Induced pluripotent stem cells do not require the use of human embryos and have the added advantage of producing patient‐specific cardiomyocytes, allowing both generic and disease‐ and patient‐specific pharmacological screening, as well as drug development through disease modelling. A critical question is whether sufficient standards have been achieved in the reliable and reproducible generation of 'adult‐like' cardiomyocytes from human fibroblast tissue to progress from validation to safe use in practice and drug discovery. This review will highlight the need for a new experimental system, assess the validity of human induced pluripotent stem cell‐derived cardiomyocytes and explore what the future may hold for their use in pharmacology. LINKED ARTICLES This article is part of a themed section on Regenerative Medicine and Pharmacology: A Look to the Future. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2013.169.issue-2